Socio-Economic Analysis of Artisanal Fisher Folks in Ogun Water-Side Local Government Areas of Ogun State, Nigeria (Global Journal of Science Frontier Research, 2012)
This study was conducted to evaluate the socio-economic analysis of artisanal fisher folks in Ogun Waterside Areas, Ogun State using structured interview guides to collect primary data randomly from eighty respondents in four fishing communities (Iwopin, Oni, Makun-omi and Agbalegiyo) in 2011 fishing season. The information collected was analyzed using descriptive and budgetary analysis. The results reveals that almost average (53.8%) of the fisher-folks were males while 81.2% were in the active age distribution of 20-60 years, no formal education (60.0%) while 37.5% are in the bracket of 11-20 year fishing experiences, married (91.3%) and (68.8%) are not members of any fisher cooperative societies. Most (71.4%) of the fisher folks inherited the fishing knowledge within the household. The total revenue (N83,762.50), Benefit Cost Ratio (0.45) and Gross Margin Ratio (49.30) showed profitability of fishery business. Constraints faced artisanal fisher folks includes inadequate storage (96.3%), infestation by water hyacinth (93.8%), inadequate power (88.8%), inadequate technology (87.5%), inaccessible credits and high cost of fishing inputs.
Keywords: artisanal fishing; fisheries; households; Nigeria; socio-economic analysis